A United States Information Agency e sua ação no Brasil de 1953 a 1964 - Santomauro, Fernando [UNESP] (2015)
Brazil-United States relations had been intensified after the XXth Century, also because of the exchanges promoted by the governments of those countries, that led to a converging way of seeing the world in several times during this period. The purpose of this thesis is tell the history of part of those relations from the second half of that century, in the context of Cold War, through the formation of the United States Information Agency (USIA) in 1953, and its actions in Brazil until 1964, the year of the military coup d'etat. The main source for this thesis development was the consultation of the American and Brazilian archives in Washington DC, New York and Rio de Janeiro, and also of studies from relevant actors of that period. The USIA, until then the American agency with the broadest representation outside the country, was an example of how the United States, even in one of the most critics moments of its History, had made the choice of investing and sophisticating the information and propaganda programs in other countries, as an complementary tool of its Foreign Policy. The case of USIA in Brazil is emblematic, for its capacity of acting and influencing several and heterogeneous groups of the Brazilian society according to the American interest, during a fundamental period of Brazilian History, from 1953 to 1964.